Explainable AI Modeling and Simulation System and Method - KIM YOUNG HEE; CHUN KI PEUM; LEE BYUNG MIN; KIM JONG MOON (2020)
Provided are a system and method for generating an artificial intelligence workflow model in which image conversion, measurement (image processing), and image searches (image search engine) can be performed, by selecting/combining algorithms suitable for a workflow having been created/modified according to a subject area such as a display manufacturing process or the like, and conducting a simulation. An explainable artificial intelligence modelling and simulation method according to an embodiment of the present invention comprises the following steps of: designing an artificial intelligence workflow model once algorithms suitable for a workflow having been created/modified according to a subject area are selected from algorithms stored in advance; and conducting, when input information is input, a simulation of the artificial intelligence workflow model for the input information. Accordingly, as described above, according to embodiments of the present invention, it is possible to visualize connections between algorithms on a workflow basis and automatically assess performance thereof through an integrated simulation, and it is also possible to perform performance comparison by simultaneously conducting simulations of multiple artificial intelligence algorithms on a workflow basis. In addition, an improvement direction for the performance of the algorithms can be suggested by enabling causes/basis of classification analysis results to be described with images and standardized shape data (feature). 디스플레이의 제조공정 등의 주제 영역에 맞게 작성/편집된 워크플로우(Workflow)에 적합한 알고리즘을 선택/조립하여 이미지 변환, 계측(Image Processing) 및 이미지 검색(Image Search Engine)이 가능한 인공지능 워크플로우 모델을 생성하고, 시뮬레이션을 수행하는 시스템 및 방법이 제공된다. 본 발명의 실시예에 따른 설명 가능한 인공지능 모델링 및 시뮬레이션 방법은 기저장된 알고리즘 중 주제 영역에 맞게 작성/편집된 워크플로우(Workflow)에 적합한 알고리즘이 선택되면, 인공지능 워크플로우 모델을 설계하는 단계; 및 입력정보가 입력되면, 입력정보를 대상으로 인공지능 워크플로우 모델에 대한 시뮬레이션을 수행하는 단계;를 포함한다. 이에 의해, 이상 설명한 바와 같이, 본 발명의 실시예들에 따르면, 워크플로우 기반으로 알고리즘의 연결을 가시화하고 통합된 시뮬레이션으로 자동 성능 검증할 수 있으며, 워크플로우 기반의 복수의 인공지능 알고리즘을 동시에 시뮬레이션하여 상호 성능 비교를 할 수 있다. 또한, 분류 분석의 결과가 이미지와 표준화된 형상 데이터(Feature)로 원인/근거를 설명할 수 있게 하여 알고리즘의 성능 개선방향을 제시할 수 있다.